In vitro callogenesis from Cedrela fissilis leaves - Menezes, A. P.; Almeida, J. C. C.; Mergener, R. A.; Gerber, T.; Schneeberger, A. H. (Scientific Electronic Archives, 2016)
The Cedrela fissilis is a species native to Brazil which offers great economic value for its high quality wood as well as medicinal importance by contain therapeutic properties. Seeds were used for in vitro establishment which form submitted to four asseptic treatments that varied in relation to the time of immersion in 2.5% sodium hypochlorite. The seeds were inoculated in the culture medium Vacin & Went, supplemented with sucrose 20 g/L and 7 g/L agar. To 56 days of cultivation were removed leaves of seedlings obtained in vitro and inoculated in Vacin&Went culture medium with different combinations of growth regulators for callus induction being T1 (control); T2: 2,5Â mM ANA e 2,5 mM BAP; T3: 2,5 mM ANA e 5,0 mM BAP; T4: 5,0 mM ANA e 2,5 mM BAP. The percentage of germinated seeds was approximately 10% and the aseptic treatment showed lower percentage of contamination (78%) differed from other treatments was T4 where the seeds remained submerged during 100 minutes in 2.5% sodium hypochlorite. About the calogÃªnese treatment with combinations of 2,5 ÂµM ANA and 2,5 ÂµM BAP proved to be the most efficient for callus induction, differing from the others reaching 84% calogÃªnicos of percentage 56 days of in vitro cultivation. T1 with absence of growth regulators was the only one to present the formation of roots 26%.